Spatial distribution of intimate partner violence in Cambodia: results from the 2021–22 Demographic and Health Survey - Shaikh, Masood Ali (Frontiers in Public Health, 2025)
BackgroundMale-perpetrated Intimate Partner Violence (IPV) against women is recognized as a global public health and human rights issue. In Cambodia, the spatial aspects of IPV have not previously been explored.MethodsUsing data from the latest Demographic and Health Survey (2021–22), an analysis of IPV’s spatial distribution was conducted.ResultsThe analysis revealed clustering, with a Global Moran’s I Index of 0.223079 and a statistically highly significant p-value of <0.0001. Distinct hot and cold spots of IPV prevalence emerged, supported by kriging analysis. The southeastern part of Mondul Kiri province exhibited the highest IPV proportions, ranging from over 50 to 100%, while the western parts of Koh Kong and Preah Sihanouk provinces had the lowest IPV proportions, ranging from 0 to 5%. Large areas in the northern half of the country, as well as smaller regions in the southern provinces of Kampot, Takeo, Kandal, and Prey Veng, showed IPV prevalence proportions ranging from greater than 25 to 50%. In contrast, the lower half of the country had comparatively lower IPV prevalence, with proportions between greater than 5 and 25%.ConclusionThe observed spatial clustering of IPV and the identification of high-prevalence areas, underscore the importance of incorporating spatial analysis into IPV research. These findings can guide geographically targeted public health policies and health education programs aimed at mitigating IPV in the most affected regions.